Treatment of bacterial respiratory infections - A. D. van Eyk (South African Family Practice)
Acute respiratory tract infections are one of the most common reasons that result in general practitioner consultations. Viruses are the most common cause of both upper- and lower respiratory tract infections, however pneumonia is usually bacterial in origin. When from a bacterial origin, S. pneumoniae non-typical H. influenzae and M. catarrhalis are mostly the cause of acute otitis media, acute bacterial rhinosinusitis and acute exacerbations of chronic bronchitis, while S. pyogenes are usually the presenting organisms in acute pharyngotonsillitis. B. pertussis, C. pneumoniae or M. pneumoniae are common organisms associated with acute bronchitis and community-acquired pneumonia (atypical). Pneumonia is a serious life-threatening condition, and organisms mostly associated with it include S. pneumoniae, S. aureus, H. influenzae type b, K. pneumoniae, Legionella species or P. jirovecii. Common symptoms and signs include coughing, facial pain, fever, nasal congestion, sore throat, dyspnoea, and tachypnoea. Most of the acute uncomplicated respiratory tract infections are self-limiting in nature. It is in many instances a challenge to distinguish between acute bronchitis and pneumonia because of the similarity in presenting symptoms. Antibiotics are in many instances inappropriately prescribed to treat the infections resulting in the burden of antibiotic resistance patterns within the community. Treatment options are usually amoxicillin, amoxicillin-clavulanic acid or the 2nd or 3rd generation cephalosporins.